Biological Activities of Snowdrop (Galanthus spp., Family Amaryllidaceae) - Kong, Chee Kei; Low, Liang Ee; Siew, Wei Sheng; Yap, Wei-Hsum; Khaw, Kooi-Yeong; Ming, Long Chiau; Mocan, Andrei; Goh, Bey-Hing; Goh, Poh Hui (Frontiers in Pharmacology, 2021)
Snowdrop is an iconic early spring flowering plant of the genus Galanthus (Amaryllidaceae). Galanthus species (Galanthus spp.) are economically important plants as ornaments. Despite their popularity and economic importance, their pharmacological properties other than the most reputable neuroprotective function remain poorly attended. This review aims to highlight neuroprotective functions and bioactivities, such as antimicrobial, antioxidant and anticancer of the extracts of various Galanthus spp.. The main constituents with pharmacological action and the capability of the bioactive substances for the treatment of various diseases has been outlined. Further, the mode of actions of respective bioactive substance were reviewed and their potential for medical therapy were discussed thoroughly to support their therapeutic possibilities. This effort may inspire the development of innovative approaches for the isolation, identification, mechanism of actions and synthesis of the existing and novel active compounds from Galanthus spp. to gain a better understanding of the basis of the activity at the cellular and molecular level.